Specular optical activity of achiral metasurfaces - Plum, Eric (2016)
Optical activity in 3D-chiral media in the form of circular dichroism and birefringence is a fundamental phenomenon that serves as evidence of life forms and is widely used in spectroscopy. Even in 3D-chiral media exhibiting strong transmission optical activity, the reflective effect is weak and sometimes undetectable. Here, we report that specular optical activity at structuredinterfaces can be very strong. Resonant polarization rotation reaching 25°25° and reflectivity contrast exceeding 50% for oppositely circularly polarized waves are observed for microwaves reflected by a metasurface with structural elements lacking two-fold rotational symmetry. The effect arises at oblique incidence from a 3D-chiral arrangement of the wave's direction and the metasurface's structure that itself does not possess chiral elements. Specular optical activity of such magnitude is unprecedented. It is fundamentally different from the polarizationeffects occurring upon scattering, reflection, and transmission from surfaces with 2D-chiral patterns. The scale of the effect allows applications in polarization sensitive devices and surface spectroscopies.